Blade of the poisoner - Hill, Douglas, 1935-2007 (M.K. McElderry Books, 1987)
Twelve-year-old Jarral and three friends with strong psychic Talents fight the evil of Prince Mephtik the Poisoner, who serves the Demon- Driver.